Linguistic and Cultural Analysis of the Proverb "Honesty is the Best Policy" Expressing the English Mentality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the analysis of English folk proverbs. The proverb honesty is the best policy is analyzed in different directions and it shows what the English mentality is like.